The soul queen of New Orleans 50th anniversary [compact disc] - Thomas, Irma (Rounder Records, 2009)
Irma Thomas, the reigning Soul Queen of New Orleans, celebrates 50 years as a recording artist, fully half of them spent as one of the most significant names on the Rounder Records roster. This collection brings together many of the best songs from her Rounder years, as well as three brand new tracks.